Serum IL-6 and IL-10 levels are associated with fatal outcomes in patients with SFTS in China - Liu, Xiaoyi; Zhang, Fan; Qiao, Jinping; He, Wentao (The Journal of Infection in Developing Countries, 2025)
Introduction: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with a high mortality rate and is a public health concern. This study aimed to investigate the associations of serum interleukin 6 (IL-6) and interleukin 10 (IL-10) levels with the prognosis of SFTS patients. Methodology: A total of 95 patients with confirmed SFTS were included. Clinical and laboratory data were compared between the survival and non-survival groups. Multivariate logistic regression analysis was used to assess independent risk factors for mortality. The predictive efficacies of laboratory markers were evaluated using receiver operating characteristic (ROC) curves. Survival analysis was performed using Kaplan‒Meier curves based on the log-rank test. Results: The levels of IL-6 and IL-10 at admission were significantly greater in the non-survival group than in the survival group (p < 0.05). Multivariate logistic regression analysis indicated that the IL-6 and IL-10 levels, estimated glomerular filtration rate, and activated partial thromboplastin time (APTT) were independent risk factors for a poor prognosis in patients with SFTS. ROC curve analysis revealed that the IL-6 and IL-10 levels and the APTT had a greater predictive value than other measured laboratory markers. Kaplan–Meier survival analysis demonstrated that SFTS patients with IL-6 > 39.5 pg/mL or IL-10 > 45.2 pg/mL had significantly lower survival within a 30-day follow-up period. Conclusions: The levels of IL-6 and IL-10 at admission are the best markers for predicting in-hospital mortality of SFTS patients and have potential prognostic value in patients with SFTS.